Prinsip Moral Sebagai Klaim Pada Hak Cipta Dan Hak Untuk Dilupakan (Right To Be Forgotten) - Pratama, Bambang (Veritas et Justitia, 2016)
AbstractIn this current digital era, the issue how to protect private-personal electronic or digital data creates the need for the recognition of a new legal right (right to be forgotten/right to delete). Legal recognition of this right must be balanced with the duty of internet service provider to control and monitor the dispersion of negative content (resulting in copyright infringements, infringements of the sanctity of personal-private data, etc.).  With the amendment of Law No. 11 of 2008 re. Electronic Information and Transactions, it becomes appropriate to discuss the right to be forgotten in terms of moral principles. The existence of this moral right is reflected in the legal protection of copyright as well as protection of private-personal data.  The main argument here is that moral principle or right as part of natural law should be used to explain the existence and importance of the right to be forgotten.